(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
The seeds of pumpkin (Cucurbita maxima Linn.) can be utilized as both a conventional and multifunctional dietary constituent. In this study the antioxidant, antibacterial, and cytotoxic effects of various fractions such as petroleum ether soluble fraction (PESF), chloroform soluble fraction (CFSF), dichloromethane soluble fraction (DCMSF), and aqueous soluble fraction (AQF) were obtained from crude extract (CE) of the C. maxima seeds were assessed by using 1,1-Diphenyl-2- Picrylhydrazyl (DPPH) method, disc diffusion technique, and brine shrimp lethality bioassay respectively. The results showed that all the fractions have remarkable antioxidant, antibacterial, and cytotoxic activities. The study revealed that both the AQF and PESF and the CF confirmed significant antioxidant properties. The antibacterial activity of different fractions against Gram-positive and Gram-negative bacteria was examined to determine their significant effect. PESF and CFSF fractions exhibited substantial inhibitory activity against Gram-positive bacteria, particularly Bacillus cereus. Bacillus subtilis exhibited significant susceptibility to both CFSF and AQF. Salmonella typhi and Shigella dysenteriae exhibited significant susceptibility to PESF and CFSF, while Escherichia coli was the Gram-negative bacterium most effectively inhibited by CFSF. The IC50 values revealed that the DCMSF exhibited the highest inhibitory activity, followed by other fractions. The new study emphasizes the significance of pumpkin seeds in terms of their pharmacological and biological properties, which may encourage more research on the potential benefits of this plant for human health. Jagannath University Journal of Life and Earth Sciences, 9(1): 7-18, 2023 (June)